A influência da renovação da frota de veículos na qualidade do ar em Curitiba - Escuciatto, Edson (2016)
Air pollutants have diverse sources, however in most urban centers fossil fuel vehicles are the main cause of this pollution. Air pollution is transported by air currents, and therefore the location of air quality monitoring stations is important in its study. In 1986 IBAMA created the Program for the Control of Air Pollution by Automobiles, establishing the maximum emission limits. The most important technologies for the reduction of pollutants in automobiles were the electronic control of fuel injection and the use of catalytic converters in the exhaust system of vehicles. The starting point of this study was the fact that newer vehicles are less polluting due to the use of more efficient technologies than those of older vehicles, and that the renewal of the fleet entails an important reduction in emissions. Therefore, the main goal was to determine if the fleet renewal altered the air quality in Curitiba. Data on the concentration of air pollutants in Curitiba between 2003 and 2014 was surveyed. The Ouvidor Pardinho Air Quality Monitoring Station was considered to be the most representative for data on the concentration of air pollutants for the purpose of this study. The surveying of the vehicle fleet of Curitiba was performed based on data from DETRAN-PR, mainly automobiles, motorcycles and diesel vehicles. Afterwards, analysis and comparison were performed. With the analysis of the DETRAN-PR data on the city’s fleet and the IAP data on air pollutant concentrations it was confirmed that there has been a renewal of the fleet in the city and that despite the increase in the size of the vehicle fleet in the surveyed time frame, there has been a reduction in the pollutant concentrations in this capital.